The prevalence of occupational health problems in-flight crews (pilots and flight attendants: A systematic review and meta-analysis - Omran, Foad (Department of Public Health and Family Medicine, 2024)
Background: The International Civil Aviation Organisation (ICAO), a United Nations (UN) body, reports that the “global air transport network” doubles in size, at least, every 15 years. Researchers have become increasingly aware that aircrew members (ACMs) are at high risk for several diseases when compared to the general population. We conducted a systematic review and meta-analysis to estimate the prevalence of occupational health problems in aircrew members (pilots and flight attendants) as compared with the general population. Methods: We identified relevant literature by searching several electronic databases including PubMed, EBSCOhost: CINAHL, PsycINFO, Web of Science, Scopus and Google Scholar and included all observational studies reporting occupational health problems among ACMs. We included published and unpublished cross-sectional studies reporting the prevalence rate of any OHPs among commercial ACMs and/or its risk factors. Articles in any language, irrespective of the date of publication, were taken into consideration. The main outcome was the prevalence of OHPs and its related factors among ACM. Meta-analysis (random-effects model) was employed to derive the summary estimate; subgroup analysis was conducted, given the high heterogeneity. Study quality was assessed using the modified Hoy et al Scale for cross-sectional studies and the National Institutes of Health (NIH) Quality Assessment Tool for Observational Cohort studies. The study protocol was registered in PROSPERO (CRD42020167631). Results: Our search of the literature addressing occupational health among commercial ACMs returned 846 studies, of which 51 articles were included in our systematic review and metaanalysis. The studies were published between (1996 - 2021) and most were cross-sectional in design (n=47) while 4 studies estimated the incidence of occupational health diseases or mortality from different sources. ACMs had various OHPs and workplace accidents and injuries were relatively common. The Pooled Prevalence Rate (PPR) by subgroup analysis showed the second most common OHPs to be Fatigue/Sleep related disorders(FSDs) (diseases or symptoms), which was higher in cockpit crew [PPR=66.64%, 95% confidence interval (CI): 52.65%–79.29%] compared to cabin crew [PPR=44.45%, 95% CI: 31.78%–57.49%]. Cabin crew had higher prevalence rates of respiratory conditions [PPR=24.08%, 95% CI: 14.18%– 36.64%] compared to cockpit crew [PPR=14.61%, 95%l CI: 4.47%–29.20%]. Musculoskeletal disorders (MSDs) were also commonly reported in cockpit crew [PPR=25.78%, 95% CI 10.31– 45.27]), cabin crew [PPR=36.90, 95% CI 25.51–49.08] and increased in ACMs [PPR=72.08%, 95% CI: 67.82%–75.97%]. The PPR of neurological conditions was found to be 13.42%, 95% CI:2.30%–31.55% in cockpit and 22.33% ,95% CI:9.69%–38.34% in cabin crew. The PPR for ENT conditions was 28.28% ,95% CI:25.96%–30.67% in cockpit and 26.8% ,95% CI:19.88%– 34.36% in cabin crew. The PPR for gastrointestinal was 40.14% ,95% CI:24.05%–57.40% in cockpit and 17.29% ,95% CI:16.31%–18.33% in cabin crew. Metabolic disorder prevalence was 19.76% ,95% CI:9.43%–32.72% in cockpit and 37.13% ,95% CI :21.70%–54.04% in cabin crew. The PPR for other conditions were relatively lower and fewer studies reported on these; cardiovascular disease prevalence was 2.42% ,95% CI: 1.99%–2.94 %in cabin crew; ophthalmological disorders 18.93%,95% CI: 18.03%–19.84% in cabin and 2.80%,95% CI: 2.32%–3.38% in cockpit crew; Cancer 0.37% ,95% CI:0.20%–0.69% in cockpit and 17.11% (95% CI:16.12%–18.14%) in cabin crew. PPR for occupational injuries was low at 0.83% ,95% CI:0.69%–0.97% in cockpit and high at 48.14%,95% CI:42.73%–53.48% in cabin crew whilst for sexual harassment it was 24.01% ,95% CI:12.64%–37.65% in cabin crew. Conclusion: There is a high prevalence of work-related illness and injuries among aircrew members supporting the hypothesis that they are at increased risk. This is the first systematic review that addresses the occupational health status of aviation personnel and it found the most prevalent problems in cockpit crew to be FSDs, gastrointestinal disorders, MSDs, ENT disorders and respiratory disorders. For cabin crew the most prevalent conditions were FSDs, occupational injuries, metabolic disorders, MSDs and sexual harassment. Governments, businesses and policy makers should support efforts to improve occupational health and safety measures among this occupational group.